Determinasi Kinerja Sumber Daya Manusia Pada Generasi X di PT. Pungkook One Grobogan - Hilda Candra Afitra Atrianto; Qristin Violinda; Ratih Hesty Utami (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study is to determine whether there is influence from information technology, task technology fit and transfer of knowledge on HR performance. This research takes the object of PT.Pungkook One Indonesia which is located in Grobogan, which has a total of 100 employees. The sampling technique used is probability sampling technique using random sampling as well as to facilitate researchers in selecting respondents. Methods of data analysis using multiple regression. The results of the study found that there was a significant effect of information technology on the performance of generation X human resources, there was a positive and significant effect of Task Technology Fit (TTF) on the performance of generation X human resources. And there was a significant effect of knowledge transfer on the performance of generation X human resources.